Examining volumetric gradients based on the frustum surface ratio in the brain in autism spectrum disorder. Issue 4 (9th December 2020) - Mann, Caroline; Schäfer, Tim; Bletsch, Anke; Gudbrandsen, Maria; Daly, Eileen; Suckling, John; Bullmore, Edward T.; Lombardo, Michael V.; Lai, Meng‐Chuan; Craig, Michael C.; ,; Baron‐Cohen, Simon; et al.
Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that is accompanied by neurodevelopmental differences in regional cortical volume (CV), and a potential layer‐specific pathology. Conventional measures of CV, however, do not indicate how volume is distributed across cortical layers. In a sample of 92 typically developing (TD) controls and 92 adult individuals with ASD (aged 18–52 years), we examined volumetric gradients by quantifying the degree to which CV is weighted from the pial to the white surface of the brain. Overall, the spatial distribution of Frustum Surface Ratio (FSR) followed the gyral and sulcal pattern of the cortex and approximated a bimodal Gaussian distribution caused by a linear mixture of vertices on gyri and sulci. Measures of FSR were highly correlated with vertex‐wise estimates of mean curvature, sulcal depth, and pial surface area, although none of these features explained more than 76% variability in FSR on their own. Moreover, in ASD, we observed a pattern of predominant increases in the degree of FSR relative to TD controls, with an atypical neurodevelopmental trajectory. Our findings suggest a more outward‐weighted gradient of CV in ASD, which may indicate a larger contribution of supragranular layers to regional differences in CV. Abstract : During human brain development, the grey matter volume (CV) expands extensively, leading to formation of the gyral‐sulcal pattern of the cortical surface. Given the folded architecture of the cortex, the distribution of CV at a given location on the surface of the brain is likely to differ, depending on whether the cortex is outward‐folded (as in gyri) or inward‐folded (as in sulci). We have designed a novel imaging feature (FSR) to capture volumetric gradients from the outer to the inner surface of the brain, and to quantify the distortion of CV across cortical layers. This may be of relevance to neurodevelopmental disorders associated with atypical cortical expansion and lamination, as has been suggested for Autism Spectrum Disorder.